2012
DOI: 10.1016/j.matcom.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

From general state-space to VARMAX models

Abstract: Fixed coefficients State-Space and VARMAX models are equivalent, meaning that they are able to represent the same linear dynamics, being indistinguishable in terms of overall fit. However, each representation can be specifically adequate for certain uses, so it is relevant to be able to choose between them. To this end, we propose two algorithms to go from general State-Space models to VARMAX forms. The first one computes the coefficients of a standard VARMAX model under some assumptions while the second, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…State-space equations and VARMA models can be interchangeably transformed [CGHJ12], so we can refer to the generated model as state-space or VARMA model with sparse GC pattern.…”
Section: Generating Eeg Datamentioning
confidence: 99%
“…State-space equations and VARMA models can be interchangeably transformed [CGHJ12], so we can refer to the generated model as state-space or VARMA model with sparse GC pattern.…”
Section: Generating Eeg Datamentioning
confidence: 99%
“…We use standard form of the Kalman filter here, instead of (8) which has a single noise term , as these representations are generally equivalent (see Casals et al (1999Casals et al ( , 2012).…”
Section: State Space Model For Kf1 Kf1 * and Kf4mentioning
confidence: 99%
“…Remark. In Casals et al (2012), it was shown that it can be possible to find a matrix T (see the referenced paper for the corresponding algorithm) for the conversion between two state space forms ( 9) and (8), i.e. : Ã = T −1 AT , B = T −1 B.…”
Section: State Space Model For Kf1 Kf1 * and Kf4mentioning
confidence: 99%
“…The state space model in (2) and (3) can be written as an observationally equivalent vector ARMA model, see, e.g., Shumway and Stoffer (1982) and Casals et al (2012). For the present case, define first the characteristic polynomial to (1),…”
Section: Equivalent Arma Parametrizationmentioning
confidence: 99%
“…The additional MA parameters (B 1 , , B k , ) are found from ( , , 1 , , k−1 , H * , G) by matching the variance structure of (7) and (8), see Casals et al (2012) for an explicit algorithm. For a model with k = 1, i.e., A(z) = I p − A 1 z with A 1 = ( + I p ), this amounts to solving…”
Section: Equivalent Arma Parametrizationmentioning
confidence: 99%